IOC OLYMPIC SOLIDARITY PROGRAMS AND TURKISH NATIONAL OLYMPIC COMMITTEES'S (TMOK) IMPLEMENTATIONS - Pınar Güzel; Selhan Özbey (Pamukkale University, 2012)
Under the supreme authority of the International Olympic Committee (IOC), the Olympic Movement encompasses organisations, athletes and other persons who agree to be guided by the Olympic Charter. IOC is regarded as the most authorized organ. One of the basic mission of the IOC is "to encourage the sport for all in every level and everywhere". The IOC -who has 205 official country member- is executed the Olympic Solidarity Programs with the Olympic Solidarity Commission. The content of these programs are to organize assistance to National Olympic Committees (NOC), in particular those which have the greatest need of it and to plan and to control. With the Olympic Solidarity World Programs, 19 programs (Athletes, trainers, NOC Management, Olympic Values) are suggested to the NOCs for developing the sport. Olympic Solidarity Commission is managed this program andthe budget with the quadrennial programs. In the 2005-2008 quadrennial plan the budget of the commission was 244 million $ and2009-2012 quadrennial plan's budget is increased with % 27.46 and it is now 311 million $. The aim of this research was; to analyze the content of the IOC Olympic Solidarity Programs and to investigate the economic inputs and level of support of these programs. Furthermore, other aim of this research was to analyze the programs and the gains of Turkish National Olympic Committe. The method of the research was descriptive model. The IOC Olympic Solidarity assist to TMOK with the Olympic sportsmen scholarship, trainers education, Olympic Education and so on. As a result of this research it was determined that Olympic Solidarity Programs support the NOCs with the areas of economic, techniqual and knowledge. Because of this it is thought of, TMOK can be take more economic support with a coherent working of this Commission. This research is the first in Turkey in terms of determine of the economic input about gainings and also profits of the level from the Olympic Solidarity Programs.